Lineare Gleichungen mit nicht beschränkten linearen Operatoren - Remeikis, S. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:С. Ремейкис. Линейные уравнения с неограниченными линейными операторамиS. Remeikis. Tiesinės lygtys su neaprėžtais tiesiniais operatoriais